El sueño chino de rejuvenecimiento nacional y la política exterior bajo Xi Jinping - Chávez Mazuelos, Jorge Antonio (2022)
Since Xi Jinping became General Secretary of the Chinese Communist Party (CCP), the Chinese Dream of National Rejuvenation has emerged as the country´s ultimate imperative. This goal stands in stark contrast to the Century of National Humiliation, when China was turned into a semi-colonial entity by way of force and compelled to cede its sovereignty andsign unequal treaties. In this article I will explain how Xi Jinping´s concept of Chinese Dream of National Rejuvenation has shifted China’s Foreign Policy approach from a low-profile orientation to a more assertive and ambitious one. Additionally, I will illustrate the role which nationalism plays in the strengthening of the party-state’s political legitimacy and how it is related to the emergence of the Wolf Warrior Diplomacy. Furthermore I will argue Xi has embraced a two-pronged foreign policy approach. On the one hand, China is portrayed asa benign major power which advocates win-win international cooperation, the creation of a Community of Shared Future and a New Model of International Relations. Nevertheless, at the same time it vows to strongly defend China’s core interests, CCP’s political legitimacy and reshape international order along the lines of Chinese political values and imperatives. Furthermore, I will illustrate how Xi has centralized power and reformed the foreign policy decision-making apparatus.